Alimentos genéticamente modificados - Ruiz Mauri, Marilia Yessenia (2022)
Genetically modified foods are nothing new. For decades, they have been altering the genetic makeup of food, saving seeds, and breeding and crossing varieties to make them tastier, bigger, and longer. Most of the food we eat today is created using traditional farming methods. However, changing crops and livestock through conventional livestock production can be time-consuming and concrete changes are difficult to achieve. After scientists developed genetic engineering in the 1970s, they were able to make these changes in more detail and in less time. The increase in the production practices of genetically modified food products has had a great impact in several countries, mainly due to their high financial interest rates. The countries that produce the most genetically modified foods lead the US, followed by Brazil, Argentina, Mexico, Canada and more. There are also countries in Europe that ban AMGs, including France, Germany, Austria, Luxembourg, you can choose not to sell, consume, import or do whatever you can with them.